Guardians in the Grey Zone: A Narrative Review of Ethical Hacking and Offensive Security Across the Medical Device Lifecycle - Alanazi, Hamed Tarqi; Aldhafeeri, Omad Naif; Alharbi, Abdullah Ali Mesfer; Alshammari, Ahmed Asi Hassan; Aljameeli, Salamah Falah; Alshammari, Mashari Saad D; Alshammari, Faisal Asi H; Alanazi, Majed Hussain M (Saudi Journal of Medicine and Public Health, 2025)
Background: The increasing connectivity of medical devices, from implantable neurostimulators to hospital infusion pumps, has exponentially expanded the attack surface in healthcare. These devices, critical to patient safety, are attractive targets for malicious actors, making robust security assessments imperative. Aim: This narrative review aims to synthesize current evidence on the application of offensive security practices—specifically penetration testing, red teaming, and bug bounty programs—throughout the total product lifecycle of medical devices, from pre-market development to post-market surveillance. Methods: A systematic search of academic databases (PubMed, IEEE Xplore, ACM Digital Library) and grey literature (regulatory documents, security advisories, conference proceedings) was conducted for literature published between 2010-2024. Results: Offensive security practices are increasingly integrated but inconsistently applied. Pre-market, penetration testing is often a compliance checkbox, while post-market, reactive bug bounty programs reveal critical vulnerabilities. A significant gap exists in proactive, continuous red teaming during the operational phase. Legal frameworks, particularly the U.S. FDA’s pre-market guidance and post-market cybersecurity directives, provide structure but lack specificity, creating ambiguity for researchers and manufacturers. Conclusion: Ethical hacking is a crucial but under-optimized component of medical device security. Moving from a compliance-centric to a resilience-centric model requires harmonized regulations, safe harbors for good-faith research, and the institutionalization of continuous offensive security as a core component of device lifecycle management.